Transfer Pricing and Enforcement Policy in Oligopolistic Markets - Oscar Amerighi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
We set up a symmetric two-country model with two multinationals competing on the quantities and possibly manipulating their transfer prices. Governments choose both the corporate profit tax rate and the level of enforcement of the "arm's length" principle. We show that stronger enforcement increases equilibrium tax rates. We also and that a larger international ownership of multinationals leads to a "race to the top" in both policies between the two countries, while trade liberalization initially implies a "race to the bottom". But as trade becomes free enough, a further decrease in trade costs raises equilibrium tax rates and enforcement policies.
Keywords: 330; Verrechnungspreis; Multinationales Unternehmen; Steuerwettbewerb; Oligopol; Rechtsdurchsetzung